Paradigma Dasar Dalam Kajian Ilmu Sosial - Noveri Faikar Urfan; Puguh Toko Arisanto; Adi Wibawa; , Al Musa Karim (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The concept of paradigm in natural sciences was introduced by Thomas Kuhn, who considered that the development of natural science paradigms, occurred in revolutionary way. This means that there is a relationship of mutual replacement between one paradigm and another. Meanwhile, social scientist, such as George Ritzer, consider paradigm not to be those introduced by Thomas Kuhn. Ritzer considers that paradigm in social sciences can be seen in divergent relation (difference views). As the result, difference view of exemplar (various findings recognized in particular paradigm), subject matters (the main issues being studied), theory (explanation or abstraction of phenomena) and methods (the rules for interpret phenomena) can be very diverse and cause debate.